Latife Tekin'in romanlarında öznellik ve anlatı - Sönmez, Ayten. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
This study aims to explore the relation between subjectivity and narrative in Latife Tekin's first five novels that received significant attention from the literary arena for the narrative style employed. In this perspective, this study searches Latife Tekin's representations of different subjectivities formed in Turkey's belated modernity experience. These collective, different and alternative subjectivities are expressed with a hybrid language in these novels. The formation of subjectivities is considered in relation to hybrid language, traditional and modern genres as well as narrative techniques. The appearance of subject as a collective entity is deepened in terms of language, space, and gender. The disintegration of subjectivity, identity, language, space, and body is explored where collectivity collapses. Finally, this work aims to locate Latife Tekin as an author and evaluate her hybrid and alternative texts.
Keywords: Turkish fiction -- History and criticism.